Cultural Analysis and Growth Kinetics of Colletotrichum circinans Causing Onion Smudge - Chauhan, Nikhil; Jarial, Kumud; Jarial, R. S.; Chauhan, Neha (International Journal of Economic Plants, 2025)
The present investigations were conducted during October, 2021 to April, 2022 under laboratory conditions in the Department of Plant Pathology, College of Horticulture and Forestry, Neri, Hamirpur. The test fungus C. circinans was isolated on potato dextrose agar from symptomatic onion bulb. Colour of mycelium was cremish white and growth was observed to be dense, cottony and suppressed. Pathogenicity test was conducted by incision method on the onion bulbs inoculated with the isolated pathogen resulted in appearance of anthracnose symptoms on inoculated part of the bulb. Different nutrient media, temperature regimes and pH levels were evaluated for the growth of Colletotrichum circinans causing onion smudge. Among six different nutrient media evaluated, potato dextrose agar gave maximum mycelial growth (90.00 mm) and growth rate (0.70 mm h-1) with pure white, cottony and fluffy mycelium exhibiting ray growth pattern after 120 hours of incubation and minimum mean mycelial growth (23.81 mm) as well as minimum growth rate (0.35 mm h-1) was recorded in Richard’s agar. Out of five different temperature regimes, 30°C was observed to be the best temperature for the mycelial growth (90.00 mm) with maximum growth rate (0.71 mm h-1) with white, strandy and cottony mycelial growth exhibiting ring pattern after 120 hours of incubation and minimum (5.00 mm) was recorded at 15°C. Among seven pH levels, pH 7.0 was observed to be the best pH for supporting the maximum mycelial growth (90.00 mm) and growth rate (0.70 mm h-1) with transparent at centre and white at margins exhibiting cottony growth with ray pattern after 120 hours of incubation and mean minimum mycelial growth (31.23 mm) was recorded at pH 5.0. The growth rate of the fungus was highest between 48–72 h of incubation in different experiments.